Linguistic impoliteness in (translated) children's fiction - Pleyer, Monika (Peter Lang, 2022)
"This book presents the first large-scale investigation of the structure and functions of linguistic impoliteness and impoliteness metalanguage in contemporary British children's fiction. The study ties together findings from pragmatics, language acquisition research, literary studies, and translation studies with novel data-driven insights. The study shows that children's fiction prefers direct, unmitigated impoliteness tokens to highlight key aspects of plot and characterisation. Impoliteness metalanguage is used to clarify impoliteness events to the child. The study provides a framework for the investigation of impoliteness in translation, which gives evidence of pragmatic differences, as well as differing views of children's cognitive abilities in two linguacultures"--
Includes bibliographical references
Keywords: Hochschulschrift; Unhöflichkeit; Höflichkeit; Sprache; Kinderliteratur; Englisch